THE EFFECTIVENESS OF USING COLLABORATIVE WRITING METHOD TOWARD STUDENTS’ WRITING SKILL OF RECOUNT TEXT AT EIGHTH GRADE SMPN 2 TEMBILAHAN - Maizarah Maizarah (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2017)
The objective of this study is to find out whether there is any significant effect between writing skill of recount text of students who are taught using Collaborative Writing and those who are taught without it and to find out the effectiveness of Collaborative Writing toward students’ writing skill of recount text at eight grade of SMP N 2 Tembilahan. The writer gave a writing test to gather the data. There were two test; pre test and post test. The formula that was used to analyze the data was t-test. The obtained t-observed was 2.79, whereas the t-table was 2.02 for a= 5%. The t-observed score was higher than the t-table (2.79> 2.02). It was meant that Ha was accepted while Ho was rejected. Since the t-observed score was higher than the t-table, the collaborative writing was an effective method for improving students’ recount writing in SMPN 2 Tembilahan. Based on the finding, the writer assumes that collaborative writing may be used as one of an alternative method in teaching writing of recount text.